PUBLIC EXPENDITURE EFFICIENCY IN PUBLIC DISTRICT SCHOOLS IN CEARÁ, BRAZIL (Gestão & Regionalidade, 2018)
This study attempts to measure the scores of technical efficiency and scale of public spending on education in Ceará. The non-parametric method used to accomplish the proposed objective consists in Data Envelopment Analysis, based on data from the Finance of Brazil system, published by the National Treasury Secretariat and Ceará's Statistical Yearbook, published by the Ceará's Institute of Research and Economic Strategy for the year 2011. The results indicate that the municipalities of Ceará may decrease their spending, in average, by 53% and 46% in models with constant and variable returns, respectively, without reducing the production of educational municipalities. In regional terms, the data indicate that the Fortaleza's metropolitan mesoregion verified the best results. Moreover, all mesoregions showed predominance of public schools operating with decreasing returns to scale. Keywords: Technical and scale efficiency; education; data envelopment analysis; Ceará.